(untitled) (American Journal of Islam and Society, 2011)
This short and concise book is presented as an important brick in the foundation of what had been designated the “Western Thought Project.” As Mona Abul-Fadl has indicated, the aim of this project was to encourage an “active” and “critical” presence of the Muslim intellect as well as promoting the “Islamization of knowledge” (vii). This was rendered necessary in light of the dilemmas facing Muslims everywhere as they strive to reconcile their religious conscience with the historical realities of a modern Western consciousness. Abul-Fadl optimistically and ambitiously perceives possibilities of shaping a “Muslim discourse on conscience” within a cooperative framework with the West ‒ in order, as she put it, to “evolve together the terms of a new global consciousness which is inclusive” (xi). This presumably would entail a dialogue, not with the West in general, but with a particular variant of it that harbors religious commonalities with Islam in terms of the givens of God, humans, history, and revelation. Abul- Fadl seeks to change the terms of the encounter from the political and the economic to the intellectual and the cultural (xiv). Summoning the intellectual community, primarily of Muslims but non-Muslims as well, is the prerequisite for the bid to renegotiate the terms of this proposed global encounter, and she asserts that the “fate of our civilization lies in the balance of culture, not power” (1). Such a “simple truth” is the premise of her study ...